IMPLEMENTASI PROGRAM PEMBINAAN BADAN USAHA MILIK DESA DI KABUPATEN SUMEDANG - Arip Rahman Sudrajat; Mira Yuliana; Nurmalasari (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2021)
It is a descriptive study with a qualitative approach. The research site was conducted on Dinas Pemberdayaan Masyarakat dan Desa Bidang Pemberdayaan Ekonomi Masyarakat Kabupaten Sumedang, Data is collected through interviews, observation, and documentation. The validity test of data using data triangulation techniques. Data is qualitative and analyzed to get a deduction. The study then USES program implementation theory and coaching theory as a guide in carrying out the study. The purpose of this study is to describe the implementation of the BUMDes development program and the factors that affect the implementation of the BUMDes development program. Research shows that implementation of the bumdes programme conducted by the associated SKPD, can the researchers conclude that it has been carried out well but not optimal through program socialization, monitoring and evaluation, directing the utilization of natural resource potential has produced quite good output, this can be seen from the increasing number of BUMDes data which shows the graph has increased from basic to developing categories. The inhibiting factor lies in the distribution of information between SKPD and village officials, and village officials and managers, which creates information disguise. there are overlapping assignments and responsibilities that hinder reporting, as well as the lack of an effective coordination forum which causes aspirations to be less conveyed. Efforts to overcome these obstacles are by involving BUMDes managers in receiving information in the form of socialization organized by the Department, creating a BUMDes application that can input every report and evaluation.